Development and characterization of a reverse genetics system for the lineage II Chicava strain of Machupo virus in a guinea pig model. - Emily Mantlo; Junki Maruyama; John T Manning; Rachel A Reyna; Cheng Huang; Slobodan Paessler (PLoS Neglected Tropical Diseases)
Background Machupo virus (MACV) is a New World mammarenavirus (hereafter referred to as "arenavirus") and the etiologic agent of Bolivian hemorrhagic fever (BHF). No vaccine or antiviral therapy exists for BHF, which causes up to 35% mortality in humans. New World arenaviruses evolve separately in different locations. To date, up to eight lineages of MACV have been identified in Bolivia. While the prototype MACV Carvallo strain belongs to lineage I discovered in the Memore Province in the 1960s, the MACV lineage II strains have become the dominantly-circulating lineage in the same province since 1993. Methods We report the development of a reverse genetics system for the MACV lineage II Chicava strain, using a pRF42 plasmid encoding the L and S segment genomic RNA under the transcriptional control of a murine DNA-dependent RNA polymerase I promoter sequence. Rescue of the recombinant MACV Chicava strain (rMACV-Chicava) was accomplished by expression of the L protein and nucleoprotein genes of the MACV Carvallo strain in trans in transfected baby hamster kidney (BHK-21) cells. We characterized the multiplication kinetics of rMACV-Chicava in African green monkey kidney epithelial Vero cells, followed by determining the virulence phenotype in outbred Hartley guinea pigs. Principal findings We demonstrated that the multiplication kinetics in Vero cells, virulence phenotype in guinea pigs, and neutralizing antibody titers are indistinguishable between rMACV-Chicava and the wild-type parental virus. Conclusion and significance We conclude that rMACV-Chicava provides a useful model system to investigate the emergence of MACV lineage II strains and the guinea pig model has utility for the development of candidate vaccines and therapeutic antibodies for BHF.